Effect of Platelet Antiserum on the Precipitation of Soluble Fibrin by Endotoxin - Müller-Berghaus, Gert; Kramer, Wilfried (Thrombosis and Haemostasis, 1976)
Rabbits were injected with a platelet antiserum to examine the role of thrombocytopenia on the precipitation of soluble fibrin by endotoxin. Platelet antiserum removed more than 98% of the circulating platelets, and the resulting thrombocytopenia with platelet counts below 10,000 per μl persisted during the entire 10 hr-period of the experiment. Leukocyte counts were not significantly influenced by the platelet antiserum. Since the rabbits were treated with high doses of heparin, activation of intravascular coagulation by the antiserum did not occur.Precipitation of soluble fibrin was achieved by injection of endotoxin into rabbits with ancrod-induced circulating soluble fibrin. Thrombocytopenia did not prevent the occurrence of glomerular microdots after ancrod and endotoxin administration. On the contrary, if endotoxin was injected into antiserum- and heparin-treated rabbits with circulating soluble fibrin, glomerular microdot formation occurred even in a higher percentage than in control rabbits treated with absorbed platelet antiserum. This investigation indicates that platelet antiserum-induced thrombocytopenia does not protect against precipitation of soluble fibrin by endotoxin.